Morfometria geométrica, dimorfismo sexual e avaliação da atratividade de Cratosomus flavofasciatus (Coleoptera: Curculionidae) ao feromônio sintético - Campos, Philippe Correia Souza (2017)
Knowledge about biology and animal behavior is critical to understanding how a particular organism interacts with its environment. Identifying the sex of individuals is an essential step in conducting behavioral studies. An integral part of animal behavior is communication, which can be intermediated by pheromones. Within different groups, insects are the animals use pheromones the most in order to carry out their fundamental activities. Cratosomus flavofasciatus, a Coleoptera of the Curculionidae family, popularly called the Orange-tree-borer, is considered one of the main citrus pests, occurring in Sergipan orchards. The objective of this work was to evaluate the morphological characteristics that allow the sexual differentiation of C. flavosfaciatus and to evaluate the attractiveness of C. flavosfaciatus to the synthetic compounds that make up the pheromone of this species. To verify the sexual dimorphism of C. flavofasciatus, a geometric morphometry analysis was first made using 80 adult individuals of each sex. There were 27 landmarks in the ventral region in each individual. The anatomical landmarks 2, 9, 10, 11, 18, 21 were the ones that contributed most to the distinction between males and females, which represent the region of the rostrum, the final portion of the abdomen and the end of the thorax. For sex confirmation, a withdrawal of the genitalia of both sexes was also performed. In females it was possible to recognize the following structures: sternite VIII and bursa copulatrix. In males, it was possible to observe the gastric spicule and the aedeagus with a pair of parammero. The Procrustes Anova showed significant differences between the sexes (P<0.001) and the size (centroid) in relation to sex (P <0.001), but there was no difference in shape in relation to size (P = 0.229) and the form in relation to sex in conjunction with the size (P = 0.707). Principal component analysis demonstrated an evident differentiation between the genders based on the ventral region of the species. The first two main components explained 51.909% (PC1 + PC2: 39.563% + 12.346%) of the shape variation. The discriminant analysis indicated a significant difference (permutation test = 10,000 permutations; P < 0.001) for the sexual dimorphism of the ventral region. The determination of the adult sex of C. flavofasciatus through the last abdominal sternum is as accurate as the dissection of the genitalia. The behavioral response of C. flavofasciatus to synthetic pheromonal compounds (a mixture of 2-((1R, 2S)-1-methyl-2-(prop-1-en-2-yl)cyclobutil)ethanol (grandisol), (E)-2-(3,3-dimethyl-cyclohexylidene)ethanol (alcohol E) and (Z)-2-(3,3-dimethyl-cyclohexylidene)ethanol (alcohol Z)) and for their host plants Cordia curassavica (Maria-Preta) and Citrus sinensis (Orange Tree) were evaluated by olfactory tests performed on a Y-tube olfactometer. Both sexes were significantly more attracted to C. sinensis stalks (P <0.05) than to filtered air. Tests with C. curassavica stalk attracted only males (P = 0.02). When the insects had the opportunity to choose between C. curassavica stalks and C. sinensis stalks, males preferred those from C. curassavica (P = 0.01), whereas females showed no significant preference (P> 0.05). The combination of the C. curassavica and C. sinensis volatiles associated with the synthetic pheromone at 100ppm concentration was more attractive for both sexes (P <0.05) than for the control (hexane together with the host plant). On the other hand, at the concentration of 10ppm, only the association with C. curassavica attracted males (P = 0.009). These results can be used as a basis for field testing, contributing to the development of an environmentally safe and effective method for monitoring orange tree borer.